Nevus Comedonicus, a Rare Case : Dermoscopic and Histopathological Findings - Nugrohoaji Dharmawan; Endra Yustin Ellistasari; Oyong Oyong; Adniana Nareswari (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Nevus comedonicus is an extremely rare adnexal hamartoma of pilosebaceous apparatus, with approximately 200 cases reported in the literature so far. It appears as cluster of adjacent honeycomb-like dillated follicular openings with firm pigmented keratin plugs resembling comedones.The comedones oftentimes arranged in linear pattern paralled to Blaschko’s lines. We report a case of a 5-year-old boy with open brown to black comedones in a linear pattern localized on the back of the left thigh that appearing since birth. Pain, itch and discharge were not obtain. There were some episodes of infection, due to manual removal done by his mother which left some hypertrophic scars. Dermoscopic examination revealed the distinctive pattern consisting of pigmented, sharply demarcated keratin plugs of 1-3 mm in diameter, some open pores, multiple structurless, various shades of brown homogenous circular areas surrounding the plugs. Histopathological examination showed an aggregation of dilated follicular infundibulum with laminated keratinous material plugging. This case report prove that dermoscopy examination, a simple non-invasive diagnostic tool is very helpful in diagnosing nevus comedonicus. We recommend this tool to differentiate the diagnosis of other rare epidermal nevi while histopathological examination should be performed only in uncertain cases.